Imaging nuclear, endoplasmic reticulum and plasma membrane events in real time. Issue 18 (10th September 2016) - Bader, Christie A.; Sorvina, Alexandra; Simpson, Peter V.; Wright, Phillip J.; Stagni, Stefano; Plush, Sally E.; Massi, Massimiliano; Brooks, Douglas A.
Abstract : Live cell imaging can provide important information on cellular dynamics; however, the full utilisation of this technology has been hampered by the limitations of imaging reagents. Metal‐based complexes have the potential to overcome many of the issues common to many current imaging agents. The rhenium (I)‐based complex fac ‐[Re(CO)3 (1, 10‐phenanthroline)(4‐pyridyltetrazolate)], herein referred to as ReZolve‐ER ™, shows promise as a live cell imaging agent with rapid cell uptake, low cytotoxicity, resistance to photobleaching and compatibility with multicolour imaging. ReZolve‐ER ™ localised to the nuclear membrane/endoplasmic reticulum (ER) and allowed the detection of exocytotic events at the plasma membrane. Thus, we present a new imaging agent for monitoring live cell events in real time, which is ideal for imaging either short‐ or long‐time courses. Abstract :